ROLE OF DIAGNOSTIC AND THERAPEUTIC GASTROINTESTINAL ENDOSCOPY (GIE) IN A PAEDIATRIC HOSPITAL AN AUDIT - De zoysa, M.I.M. (My University, 2012)
Symptoms related to gastro -intestinal tract account for a significant number of admissions to paediatric units. Therefore, upper and lower GIE becomes an important diagnostic and sometimes a therapeutic tool. However, paediatric endoscopy is still in its infancy in Sri Lanka. We are presenting the initial results of an ongoing audit.